Naso-Maxillary extramedullary plasmacytoma: A case report - Abdullah, Nazik E; Raheem, Mona A A.; Elamin, E M; Adam, Ameera A M; Hamad, K M; Hamad, Tarig A; Hassan, A M E (Gezira Journal of Health Sciences, 2013)
We report an early case of extramedullary, right maxillary sinus and nasal, plasmacytoma. The patient was a 27 years old female who presented with nasal bleeding and a nasal mass. Imaging studies showed opacities in the nasal cavity and the maxillary sinus but there was no bone involvement.  A biopsy from the nasal mass showed a plasmacytoma. She was investigated to rule out systemic disease. The investigations included; serum electrophoresis, urine analysis for Bence Jones proteins, bone marrow aspirates study and radiological skeletal survey. The results of all investigations were negative. After complete excision of the tumour endoscopically the patient was treated with adjuvant radiotherapy. She remained well, without recurrence or spread of the tumour at 4 years follow up. CTscans pre and postoperatively as well as H&E and Immunohistochemistry slides are presented. To our knowledge, this is the first case to be reported in Sudan.